Persepsi Masyarakat terhadap perkawinan Adat Dayak Kanayatn Pada masa pandemi Covid-19. - Krisna, Magdalena (Sekolah Tinggi Agama Katolik Negeri Pontianak, 2022)
This research was motivated by the rise of traditional marriages carried out by the Indigenous Peoples of the Menjalin Subdistrict, Landak Regency during the COVID-19 pandemic. From the author's search, not many of them do marriage in marriage and marriage in the State. This research was conducted using the ethnographic method in the period February-June 2021. The findings of this study indicate that the public's perception of traditional marriage is something that is legal. The Kanayatn Dayak Indigenous People see that customary marriage is more important than church and state marriage. This perception is influenced by a strong belief in their culture, where they feel more guilty towards the spirits of their ancestors if they do not carry out marriage customs compared to state marriages. Another thing is lazy administration with the church and the government. During the COVID-19 pandemic, there is also a prohibition on preparing for a traditional wedding attended by people who are limited for one reason.